introduction to structural mechanics - Smith, P.S. Paul S (Basingstoke : Palgrave, 2001)
Further problem - with solutions - aim to further bolster learning at the end of each chapter.The book will provide a powerful learning or revision tool for undergraduate civil engineering or building students.
Preface.- Introduction & Load Path.- Section Properties and Moment of Resistance.- Analysis of Beams.- Analysis of Three Pin Frames.- Deflection of Beams and Frames.- Pin Jointed Frames.- Torsion and Torque.- Combined Stress.- Index.
Includes index.
Keywords: Structural analysis (Engineering)